The Impact of Online Reviews and Influencer Endorsements on Consumer Purchase Decisions - M. Mujahid (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
This research examines the impact of online reviews and influencer endorsement on consumer purchase decisions, exploring the mediating role of consumer trust and the moderating role of brand familiarity in these relationships. A quantitative approach, guided by a positivist research philosophy, is adopted. The research population consists of customers of online brands, and a convenience sampling technique was employed to target a relevant group of participants (300). Data was collected using a survey questionnaire. For data analysis, SPSS and Smart PLS SEM are used to examine the relationships. The findings of the research reveal that online reviews significantly impact consumer purchase decisions, with positive reviews enhancing the likelihood of purchase. Similarly, influencer endorsement is found to have a substantial effect on purchase decisions, with influencers acting as trusted sources of information for consumers. The study also highlights that consumer trust plays a crucial mediating role between online reviews, influencer endorsements, and purchase decisions. Furthermore, brand familiarity moderates the relationship between these factors and purchase decisions, with consumers being more likely to trust familiar brands. In conclusion, both online reviews and influencer endorsements are vital factors influencing consumer purchasing behavior, and consumer trust and brand familiarity further enhance these effects.